PHYSICO-CHEMICAL AND BACTERIOLOGICAL QUALITY OF WATER FROM WATER SOURCES AND HOUSEHOLD DRINKING WATER AT NAKIVALE REFUGEE BASE CAMP, SOUTH-WESTERN UGANDA, A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Sadrack Omara; Mackline Alinda; Ronald Eyul; Marvin Thomas Opiyo; Daniel Victor Kaweesa; Christopher Okeny; Enoch Muwanguzi (Student's Journal of Health Research, 2023)
Introduction: Safe drinking water and sanitation are indispensable to sustain life and health, adequate, safe, and accessible water supply are fundamental to the dignity of all. This study determined the physico-chemical and bacteriological quality of water supplied to the fragile community in Nakivale Refugee Base Camp, Southwestern Uganda. Methodology: Physico-chemical properties were measured in situ using Hanna Instrument HI 98129. Multiple tube technique was employed to determine the presumptive coliform counts. Positive samples for coliforms were incubated at 44oC for 48 hours in Single Strength MacConkey broth. Only positive samples were followed by conventional biochemical tests of indole, motility, and citrate to identify E. coli. Results:  The mean temperature, Total dissolved solids, pH, and electrical conductivity for both the water sources and household water samples were 23.79±1.04oC and 25.25±0.38, 289.07±153.45 and 433.31±519.13, 7.81±0.31 and 6.65±0.35 and 547.8±315.73 and 768.52±397.71 respectively. Among the water sources sampled, 43% (13) were contaminated with total coliform bacteria, and 10% (3) were positive for E. coli. 90% of household samples were contaminated with coliform bacteria with 11% positivity for E. coli. 61% (103) of the participants did not use water treatment. 19% (32) used boiling and 19% (32) used chlorination methods while 1% used filtration. Conclusion: Physico-chemically, all water samples had temperatures above the WHO guidelines for palatable water i.e. <15oC. Bacteriologically, Water samples were contaminated and not fit for human consumption hence the need for effective water treatment and proper post-treatment practices.  Recommendation: Nakivale refugee base camp occupants need continuous training on water treatment methods, safe water handling practices, and proper handling of fecal waste to minimize fecal water contamination. Further studies should be conducted to assess the effect of storage of clean vessels as an intervention on the bacteriological quality of water.